Batman begins - Nolan, Christopher, 1970-; Bale, Christian, 1974-; Caine, Michael; Neeson, Liam.; Holmes, Katie; Oldman, Gary.; Pfister, Wally; Zimmer, Hans.; Howard, James Newton; Kane, Bob.; DC Comics, Inc.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2005)
As a boy a young Bruce Wayne watched in horror as his millionaire parents were slain in front of his eyes. This trauma led him to become obsessed with revenge. After disappearing to the East where he seeks counsel with a ninja cult leader, he returns to his now decaying Gotham City. The City is now overrun by organized crime and dangerous individuals manipulating the system. The discovery of a cave under his mansion, and a prototype armoured suit leads him to take on a new persona. He becomes Batman and strikes fear into the hearts of men who do wrong. With the help of rising cop Jim Gordon, Batman sets out to take down the various criminal schemes that have been set in motion by individuals such as mafia don Falcone, the twisted doctor/drug dealer Jonathan 'The Scarecrow' Crane, and a mysterious third party that is quite familiar with Wayne and waiting to strike when the time is right.
Title from container.
Based on the characters created by Bob Kane and DC Comics.
Special features: 'Batman begins' mobile game demo; Web links.
Director of photography, Wally Pfister ; editor, Lee Smith ; music, Hans Zimmer, James Newton Howard ; costume designer, Lindy Hemming ; production designer, Nathan Crowley.
Christian Bale, Michael Caine, Liam Neeson, Katie Holmes, Gary Oldman, Cillian Murphy, Tom Wilkinson, Rutger Hauer, Ken Watanabe, Morgan Freeman.
MPAA rating: PG-13; for intense action violence, disturbing images and some thematic elements.
Keywords: Batman (Fictitious character) -- Drama; Organized crime -- Drama; Criminal behavior -- Drama; French language materials; Spanish language materials; Feature films; Superhero films; Video recordings for the hearing impaired